KONFIGURASI IDENTITAS DAN PARTISIPASI PUBLIK DALAM TWITTER - Endang Suryana Priyatna (Fakultas Komunikasi, Sastra, dan Bahasa, 2012)
Living in a globalized world where information dominates every a pect of life, our access to social reality seems to be in a mediated by media. Whether it is realized or not, media constructs our perceptions and rea tions toward the reality through representations it projects. Out of so many things mediated by the media, representation of certain identities is one example of how media constructs our perception. Through the narration and narrative it creates and narrates, media constructs and represents certain perceptions towards the objects and subjects of representations. From this context, we can argue that media holds ‘a regime of truth’ or an apparatus of institutions which hold power over access to knowledge, access to reality. However, the uprising of internet as the new media gives a new construction and configurations towards the mediations and modes of representations.Applying theories on the new media proposed by Mark Poster and Katherine Hayles, the research is focused and contextualized toward the analysis of Twitter as one of social media in the internet environment. The analysis is directed toward how certain identities are being represented and how the representation is reacted. Contextualizing to twitter user in Indonesia, I take the representation of two opposing Islamic group: Islamic Defender Front (FPI) and Liberal Islam Network (JIL) as my analysis. The research shows that 1) the representation and reaction toward those two groups in Twitter is constructed through user anonymity and parody, image disappropriation and caricatures, and hash tags. 2) These modes of representations cannot be separated from the existing stereotypes of those groups. 3) The old media’s role in constructing the representation is by giving certain basic assumptions about those groups.